1294. Acceptability and Feasibility of a Pharmacist-led Pre-exposure Prophylaxis Program in the Midwestern United States. (26th November 2018) - Bares, Sara; Havens, Joshua; Scarsi, Kimberly; Klepser, Donald; Swindells, Susan
Abstract: Background: Despite evidence that HIV pre-exposure prophylaxis (PrEP) substantially reduces the risk of infection in at-risk populations, significant barriers exist to its prescription and use. Utilizing pharmacists may help increase patient access to PrEP services. We designed and implemented a novel pharmacist-led PrEP program in Omaha, Nebraska. Methods: Our pharmacist-led PrEP program was developed in the fall of 2016. Six pharmacists from four sites (one community pharmacy, two community-based clinics and one HIV-specialized clinic) were selected for participation based on interest, senior management support, and availability of appropriate infrastructure. All pharmacists received training for the provision of PrEP. Through a collaborative practice agreement, pharmacists met with patients individually, obtained a medical history, performed a risk assessment and point-of-care laboratory testing (HIV screen, creatinine, and syphilis), and collected samples for gonorrhea and chlamydia. They also provided medication and adherence counseling, and prescribed emtricitabine-tenofovir DF when appropriate. Pharmacists completed a survey reporting their experience after each visit. Presented here are patient demographics, retention rates, and pharmacist-reported experience from the first 6 months of the program. Results: Sixty patients enrolled in the pharmacist-led PrEP program between January and June 2017 and completed 139 visits. 95% of participants were men, 83% were white, 80% were privately insured, and 90% had completed some college or higher. The mean age of participants was 34 years (range 20–61 years) and 88% identified as men who have sex with men. 73% were retained in care at 3 months and 58% were retained in care at 6 months. To date, no patient has seroconverted. Pharmacists reported feeling comfortable performing point-of-care testing at all visits and only reported feeling uncomfortable counseling patients on three occasions (2.2%). Finally, pharmacist-reported workflow disruption only occurred on 1 occasion (0.7%). Conclusion: Implementation of a pharmacist-led PrEP program is feasible, associated with high rates of pharmacist acceptability, and results in retention rates that are comparable to other real-world PrEP programs. Disclosures: S. Bares, Gilead: Grant Investigator, Grant recipient. S. Swindells, Merck: Investigator, Research support. ViiV: Investigator, Research support.